Re-evaluation of critical concentrations of antituberculosis fluoroquinolones in the Mycobacteria Growth Indicator Tube 960 system - Praharshinie Rupasinghe; Michele Driesen; Jens Vereecken; Bouke C de Jong; Leen Rigouts (International Journal of Mycobacteriology, 2023)
Background: Fluoroquinolones (FQs) have substantial activity against the Mycobacterium tuberculosis complex (MTBc) by preventing bacterial DNA synthesis through DNA gyrase inhibition. The reference standard for FQ-resistance testing is phenotypic drug-susceptibility testing (pDST) based on growth inhibition of MTBc in drug-containing Mycobacteria Growth Indicator Tube system (MGIT) media at a critical concentration (CC) that differentiates phenotypically wild-type from nonwild-type MTBc and at a clinical breakpoint that identifies strains that will likely still respond to treatment at higher doses. Despite the recent introduction of powerful new TB drugs, highly sensitive detection of clinically defined FQ resistance remains key. Method: In this study, we re-evaluated the current WHO-recommended CCs of Lfx (1.0 mg/ml), Mfx (0.25 mg/ml), Gfx (0.25 μg/ml), and the nowadays, obsolete CC of Ofx (2.0 mg/ml) for MGIT, using 147 MTBc isolates with known gyrA and gyrB sequences including both high-and low-level FQ resistance-conferring mutants. We tested a wide range of drug concentrations covering the current and former/obsolete WHO-recommended CCs for FQs and some intermediate concentrations to challenge the current WHO-recommended CCs. Results: The specificity of all four CCs was 100%. The sensitivities varied: 92.4% for Ofx and Lfx, 85.7% for Mfx, and 83.2% for Gfx. Lowering the CC of Mfx to 0.125 mg/ml would allow to correctly classify all wild-type and mutant isolates while lowering the CC of Gfx to 0.125 mg/ml would still misclassify some gyrA/gyrB mutants as susceptible. Conclusion: Based on our findings, a minimal inhibitory concentration of 0.125 mg/ml on MGIT medium is a more appropriate CC for Mfx and probably also as a surrogate for overall FQ resistance in the MTBc.